Integrative multi-omics identifies MEIS3 as a diagnostic biomarker and immune modulator in hypertrophic cardiomyopathy - He, Jinchen; Zhou, Zehua; Kong, Dejun; Zhu, Heng; Liu, Chunmei; Wang, Yuyuan; Wu, Tianqi; Chen, Jinfeng; Liao, Yan; Wu, Qi (Frontiers in Immunology, 2025)
BackgroundHypertrophic cardiomyopathy (HCM) is a prevalent genetic cardiac disorder characterized by myocardial hypertrophy and diastolic dysfunction. While traditionally attributed to sarcomeric mutations, recent studies have highlighted the pivotal contribution of immune dysregulation and stromal–immune interactions in its pathophysiology. However, the molecular drivers bridging structural remodeling and immune activation remain poorly defined.ObjectiveThis study aimed to characterize the clinical and immunological role of the transcription factor MEIS3 in HCM through integrative transcriptomic and single-cell analyses, with a focus on its diagnostic potential and regulatory interactions within the cardiac microenvironment.MethodsWe performed bulk RNA sequencing on peripheral blood samples from clinically diagnosed HCM patients (n = 4) and matched healthy controls (n = 3), followed by differential expression analysis and weighted gene co-expression network analysis (WGCNA). Machine learning algorithms (LASSO and Random Forest) were used to identify key diagnostic genes. Single-cell RNA sequencing (scRNA-seq) from myocardial tissues was used to localize gene expression. The immunological context was evaluated via xCell-based immune deconvolution, cytokine–immune cell correlation analysis, and ceRNA network construction centered on MEIS3.ResultsMEIS3 was significantly upregulated in HCM samples and identified as a core hub gene in the HCM-associated blue WGCNA module. Machine learning consistently ranked MEIS3 among the top discriminatory markers (AUC > 0.90). scRNA-seq revealed MSCs as the predominant MEIS3-expressing population in HCM myocardium. Functional enrichment implicated MEIS3 in pathways related to protein synthesis, mitochondrial metabolism, and immune modulation. Immune deconvolution indicated increased M1 macrophages, NK cells, and dendritic cells in HCM. MEIS3 expression positively correlated with key immunomodulatory cytokines (CXCL12, BMP1) and altered immune landscapes. The ceRNA network identified candidate lncRNA–miRNA–MEIS3 axes potentially driving its overexpression. Cytokine–immune cell analysis revealed MEIS3-linked cytokines bridging stromal and immune compartments, reinforcing its central role in immunoregulatory remodeling.ConclusionMEIS3 functions as a stromal-centric immunomodulator in HCM, shaping cytokine expression and immune infiltration in the diseased heart. Its expression shows diagnostic potential and may represent a novel target for immuno-modulatory strategies. These findings open new avenues for immuno-targeted interventions in HCM management.